Patient-centered communication’s association with trust, satisfaction, and perception of electronic health records use among newly diagnosed patients with cancer - Elkefi, Safa; Asan, Onur; Yu, Zhongyuan; Yen, Tina; Rowley, Scott (Frontiers in Communication, 2024)
The diagnosis of cancer creates immediate psychosocial distress for patients. New cancer patients are required to make important decisions about their treatment. Thus, it is essential to investigate their communication needs. This study examines the association between patient-centered communication and newly diagnosed cancer patients' trust in their healthcare providers, satisfaction with the care visits, and perception of technology use during the visits. We collected data from the Hackensack Meridian Health between February 2021 and May 2022. One hundred thirty-five participants were included in the study. The findings captured the significant effect of patient-centered communication on the trust in doctors and satisfaction with care services. However, no association was noticed with the perception of EHR use among this population. In the first visits after cancer diagnosis, patients need to build strong communication with their doctors to build trust in them. Future studies should focus on testing the hypotheses longitudinally to validate the findings in other phases of the cancer care continuum.